2005
DOI: 10.18267/j.pep.250
|View full text |Cite
|
Sign up to set email alerts
|

Financial Integration and the New EU Member Countries: Challenges and Dilemmas

Abstract: Abstract:Real convergence is the key economic challenge for the new EU Member Countries. The main growth area today is the "new" entrepreneurial economy of creativity and innovation. But such an economy needs a financial structure capable of coping with the higher risk inherent in the "new" economy. To provide such a financial structure, the financial markets must be broad, deep and liquid, i.e. financial markets must be large enough to provide this financial structure. Hence, the financial integration became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The econometric model is in line with previous researches done by Vo, and Daly (2007) and Lane and Milesi-Ferretti (2003;2006) and employs the several control variables in a model as follows: VAFATVA, FINFREED and tax rate. A dynamic panel model was chosen because it was much less employed in the previous research about financial integration and because this estimator is suitable for the analysis of a linear relationship, in which the dependent variable is dynamic, that is, dependent on its own past values, and when the independent variables are not strictly exogenous.…”
Section: Methodology and Datasupporting
confidence: 56%
“…The econometric model is in line with previous researches done by Vo, and Daly (2007) and Lane and Milesi-Ferretti (2003;2006) and employs the several control variables in a model as follows: VAFATVA, FINFREED and tax rate. A dynamic panel model was chosen because it was much less employed in the previous research about financial integration and because this estimator is suitable for the analysis of a linear relationship, in which the dependent variable is dynamic, that is, dependent on its own past values, and when the independent variables are not strictly exogenous.…”
Section: Methodology and Datasupporting
confidence: 56%
“…The econometric model is in line with previous researches done by Vo, and Daly (2007) and Lane and Milesi-Ferretti (2003;2006) and employs the several control variables in a model as follows: VAFATVA, FINFREED and tax rate.…”
Section: Methodology and Datasupporting
confidence: 56%
“…A dynamic panel model was chosen because it was much less employed in the previous research about financial integration and because this estimator is suitable for the analysis of a linear relationship, in which the dependent variable is dynamic, that is, dependent on its own past values, and when the independent variables are not strictly exogenous. It takes into account the specificity of each observation unit and allows heteroskedasticity and autocorrelation within the observation units, but not among them (Roodman, 2006). Moreover, due to the dynamic nature of financial integration as dependent variables and the characteristics of sample, the estimation of parameters was made using the Generalized Method of Moment (GMM) approach with the verification of Sargan test statistics and Arellano-Bond tests.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Their findings indicate that there is a statistically significant link between advanced financial markets and FDI inflows. Several studies have aimed to understand the factors that influence international financial integration in countries undergoing transition (Voronkova, 2004;Kučerová, 2009;Rusek, 2005). Voronkova (2004) used Gregory and Hansen's co-integration approach to examine the effects of IFI in several European countries including the Czech Republic, Hungary, Poland, the United Kingdom, France, Germany, and the United States, and found that the markets in Central and Eastern Europe (CEE) were becoming increasingly integrated with the global economy.…”
Section: Literature Reviewmentioning
confidence: 99%